Quality Control Analysis of Creatinine Examination with Westgard Multi Rules and Six Sigma - Wati, Wayan Shinta; Cahyani, Anak Agung Ayu Eka; Prihatiningsih, Diah; Parwati, Putu Ayu (Future Science, 2025)
Introduction: Creatinine is an examination parameter for kidney function and can be measured by several methods. Quality control needs to be done to ensure the results of the creatinine examination are correct. Objective: This study aims to determine the results of the quality control analysis of creatinine examination with Westgard multirules and Six Sigma in the clinical pathology laboratory at Wangaya Hospital, Denpasar, in 2023. Methods: This study used a descriptive research design, secondary data, and quality control results. Data analysis was done by determining the mean value, SD, CV, d%, sigma, and making the Levey-Jennings graph. The results showed that the bias value (d%) was still below the maximum value; the CV value in January, March, April, and July exceeded the maximum limit. Evaluation of Westgard's rules obtained the results of violations of trends, shifts, and 1- 2s, then variations in sigma values each month, namely <3 and >4 from June and September to December 2023. Results: Based on the results of the study, it can be concluded that creatinine examination obtained a good accuracy value, low precision value in certain months, there are random (1- 2s) and systematic (trend and shift) errors, and a low sigma value, which is <3 (unacceptable performance and poor performance categories). However, the sigma value has increased from June to September to December, which is >3 (marginal performance, good performance, and world-class performance categories). Conclusion: Accuracy and precision values must be maintained because good accuracy and precision values will increase the sigma value, especially in creatinine testing.